Structure and aerodynamic characteristics of a coaxial quad-wing flapper. (August 2021) - Shen, Huan; Li, Qian; Hu, Kun; Feng, Zhuoqun; Ji, Aihong
As a special type of micro ornithopter, the coaxial quad-wing flapper (CQWF) enables greater flight speed and higher stability than the paired-wing flapper. These characteristics are closely related to the unique pneumatic mechanism of the CQWF. Therefore, the aerodynamic generation mechanism of the CQWFs has been actively researched in recent years. This study verifies the reliability of flow-field simulations in a CQWF prototype with an aerodynamically optimized driving mechanism. For the selected motion parameters and shape dimensions of the flapping-wing aircraft, the vorticity fields at different elevation angles are observed in flow-field simulations. The elevation angle strongly affects the lift. Moreover, the wing movement based on the Clap–Fling mechanism significantly affected the acquisition of the lift, which explains the higher stability of the CQWF than that of the paired-wing flapper and provides a theoretical basis for the optimization of the flapping prototype. When tested on a wind-tunnel platform, the prototype yields slightly higher lift compared with those obtained in the simulation study. In addition to confirming the phenomenon revealed in flow visualization, it also showed that the unsteady mechanism of the two-pair wing is more powerful than calculated.